2022
DOI: 10.3389/fpsyg.2022.890395
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Learning and Academic Performance in Chilean University Students in Virtual Mode During the Pandemic: Effect of the 4Planning App

Abstract: Research on the use of smartphone apps with the aim of developing self-regulated learning (SRL) and increasing academic performance of university students in virtual mode, as a result of the COVID-19 pandemic, is recent and scarce. The present article shows the results of a study that analyzed the effect of using the 4Planning app with an intra-curricular approach on SRL and on the academic performance of 119 1st-year psychology students in virtual mode, at a Chilean university (MAge = 22.81, SDAge = 6.52). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(88 reference statements)
0
4
1
Order By: Relevance
“…In regards to the relationship between SRL and academic performance, this research presents contrasting findings from previous studies, which indicated a favorable correlation between self-regulation and academic achievement [ 9 , 38 ]. The findings of this study possess clinical significance and theoretical relevance, despite not reaching statistical significance.…”
Section: Discussioncontrasting
confidence: 90%
“…In regards to the relationship between SRL and academic performance, this research presents contrasting findings from previous studies, which indicated a favorable correlation between self-regulation and academic achievement [ 9 , 38 ]. The findings of this study possess clinical significance and theoretical relevance, despite not reaching statistical significance.…”
Section: Discussioncontrasting
confidence: 90%
“…The lowest effect value, with -8 [-13.02;-2.98], was obtained in the study on the use of WhatsApp by medical students (Clavier et al, 2019). When the sampling variance is examined, the biggest contribution was made by 5 studies (Jackson et al, 2019;Jaramillo et al, 2022;Lobos et al, 2021;Loeffler et al, 2019;Park & Kim, 2018) with 4.02%. The lowest contribution was from the study of Chang et al (2022).…”
Section: Findings Descriptive Statisticsmentioning
confidence: 97%
“…When the classification of effect sizes was made, it was determined that seven (27%) studies (Briz-Ponce et al, 2016;Clavier et al, 2019;Jackson et al, 2019;Kim et al, 2017;Park & Kim, 2018) had a small effect size. The rate of studies (Chuang et al, 2018;Jaramillo et al, 2022;Lobos et al, 2021;Loeffler et al, 2019) with a medium effect size is 15% (4). The remaining 15 studies (Alghazzawi et al, 2021;Arain et al, 2018;Bell et al, 2018;Chang et al, 2022;Chuang et al, 2018;Dabbour, 2016;Daliri et al, 2021;Jia & Chen, 2020;Kim et al, 2017;Shen, 2021;Sultan et al, 2020;Wang et al, 2022;Zakian et al, 2022) have a large effect size (58%).…”
Section: Findings Descriptive Statisticsmentioning
confidence: 99%
“…Third, there is a relationship between self-regulated learning and learning engagement. Research conducted by previous study shows that students who have self-regulated learning are able to provide the best results in their learning activities (Jaramillo et al, 2022). In an era of very rapid technological development, it becomes an opportunity and makes it easier for students to dig up information and deepen their academic knowledge.…”
Section: The Relationship Between Self-regulated Learning and Student...mentioning
confidence: 99%